Agregação de valor nutricional e sensorial em rapaduras artesanais - Joseph, Djalou (2017)
Rapadura is a traditional product made from sugar cane juice (Saccharum officinarum L.). It is very popular in Latin America and the Caribbean, particularly in Haiti, where it is commonly used by the rural population. It is an energy food has a low content of basic nutrients (proteins, fibers and fat). The objective of this work was to aggregate nutritional and sensorial value in artisan shavings, to evaluate the effect of the addition of ingredients in both the nutritional value and the acceptance of the product and comparing with a biscuit that is a delicacy sold in Haiti. Five formulations of artisan rapaduras were analyzed in fiber, fat, protein, moisture, ashes and submitted to sensory analysis preferably in relation to color, aroma, taste, body, overall impression and purchase intention. For the physico-chemical characteristics, the results showed that the enrichment produced rapadura containing higher levels of protein and fat (with peanut, coconut grated and sesame) and a considerable percentage of fiber (with peanuts and sesame). Regarding the sensory characteristics, the means of the judgments for the different samples for each variable remained above the average on a scale of 1 to 9 or of 1 to 5 for purchase intention, regardless the type of ingredients added. Thus, enriched rapadura is a promising alternative as a nutritious delicacy from the family farming, available for populations like in Haiti in which the family farming occupies a prominent place.